PERLINDUNGAN HUKUM BAGI PEMENANG LELANG ATAS TANAH SEBAGAI OBJEK LELANG YANG TIDAK DAPAT DINIKMATI - Ekwanto, Hafiz Nur; Maryano, Maryano; Hutomo, Putra (SINERGI : Jurnal Riset Ilmiah, 2025)
One of the most difficult execution processes for those seeking justice is the execution process based on the Deed of Assignment of Mortgage Rights. Obstacles that arise include when the auction buyer attempts to execute the mortgage but discovers that the mortgaged object has been leased by another party, the collateral object is in dispute with another party, or the object has been sold or transferred without the creditor's knowledge. The research questions are: How is the legal protection afforded to the auction winner for an object that cannot be enjoyed? And what are the legal consequences for the auction winner who cannot enjoy the land as the auction object? This research uses the Legal Protection Theory, which provides protection for human rights harmed by others, and this protection is provided by law. The Legal Consequence Theory, which explains the emergence of rights and obligations arising from legal relationships, whether due to legal acts such as agreements or legal events such as birth or death. The type of research used by the author in this thesis is normative juridical legal research. Research that uses entirely secondary data can be abandoned in developing a tentative theoretical framework, but developing a conceptual framework is absolutely necessary. Therefore, in developing a conceptual framework, formulations contained in statutory regulations are necessary. The theory of protection emphasizes the importance of preventive and repressive legal protection for every legal subject, including auction winners who obtain their rights through a legitimate auction process. However, its implementation in practice still shows inequality. There is still a need to improve the understanding of the community and banking parties regarding their rights and obligations in the implementation of auctions, including the importance of the principle of prudence as tested first in court so that there is legal certainty if the auction winner's application is granted, it will be ne bis in idem if it is sued again, at the time before carrying out the execution so that the legal consequences that arise can run according to the objectives of the law